(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Similar to everything else in life, higher the risk, larger is the return. Distinct from other investment options, stock market investments are riskier but the rewards are also equally handsome and attractive. The foremost reason behind such risk is market volatility or fluctuations. By nature the stock market is exceptionally erratic. Many times for unknown reasons the shares prices can go up or come down randomly. Owing to this impulsiveness, investments in such markets are deemed to be risky proposition. Nevertheless, if time is invested in properly studying the market and its randomness in detail, rewards can be reaped substantially. The foremost step towards this is to comprehend the reasons behind stock price movements. Using step-wise regression this paper examines the impact of few macroeconomic indicators on BSE Sensex. Results suggest a model where FDI significantly influences the fluctuations in the stock market in India.